Allogeneic haematopoietic stem cell transplantation with decitabine-containing preconditioning regimen in TP53-mutant myelodysplastic syndromes: A case study - Wang, Yuxin; Sun, Yao; Xie, Jing; Hu, Jiangwei; Liu, Na; Chen, Jianlin; Li, Botao; Lan, Sanchun; Niu, Jingwen; Wang, Lei; Qiao, Zhuoqing; Zhang, Yu; et al. (Frontiers in Oncology, 2022)
Myelodysplastic syndrome (MDS) with TP53 mutations has a poor prognosis after transplantation, and novel therapeutic means are urgently needed. Decitabine (Dec) monotherapy has demonstrated improved overall response rates in MDS and acute myeloid leukaemia, although these responses were not durable. This study aimed to preliminary evaluate the efficacy of a Dec-containing allogeneic haematopoietic stem cell transplantation (allo-HSCT) preconditioning regimen in TP53-mutant MDS. Nine patients with TP53-mutant myelodysplastic syndromes received the decitabine-containing preconditioning regimen and subsequent myeloablative allo-HCT between April 2013 and September 2021 in different centres. At a median follow-up of 42 months (range, 5 to 61 months), the overall survival (OS) was 89% (8/9), progression-free survival (PFS) was 89% (8/9), and relapse incidence was 11.1%. The incidence of severe acute (grade III-IV) graft-versus-host disease (GVHD) was 22.2% (2/9) and that of chronic moderate-to-severe GVHD was 11.1% (1/9). The 1-year GVHD-free/relapse-free survival (GRFS) was 56% (5/9). In conclusion, we found real-world clinical data that supports the use of a Dec-containing preconditioning regimen before allo-HSCT for possible improved outcomes in TP53-mutant MDS patients; there is therefore an urgent call for an in-depth exploration of the involved mechanism to confirm these preliminary findings.